DISKRIMINASI SOSIAL DALAM NOVEL AYAH, MENGAPA AKU BERBEDA? KARYA AGNES DAVONAR - Ridha, Fadhlina Kurnia; Asri, Yasnur; Nurizzati, Nurizzati (Universitas Negeri Padang, 2013)
The purpose of this article is (a) to describe the form of social discrimination in the novel Ayah,Mengapa Aku Berbeda? written by Agnes Davonar, (b) to describe the causes of social discrimination in the novel Ayah, Mengapa Aku Berbeda? written by Agnes Davonar, and (c) to describe the impact of living figures which are reflected in the novel Ayah, Mengapa Aku Berbeda? written by Agnes Davonar. The data sources of this study is novel Ayah, Mengapa Aku Berbeda? by Agnes Davonar. Data were collected by using descriptive methods. Research findings are form, causes, and impact of social discrimination in the novel Ayah, Mengapa Aku Berbeda? written by Agnes Davonar.